The reverse logistics process in omnichannel sales using the example of Decathlon Sp. Z o.o. - Skurpel, Dagmara; Bakalarczyk, Bartłomiej Tomasz (Contemporary challenges of transport, freight forwarding and logistics - selected aspects, 2023)
This chapter presents the issue of reverse logistics in omnichannel commerce, a sales strategy in the B2C segment based on the assumption that all available outreach, customer service and sales channels, at each stage of the transaction, should work together to ensure the convenience of the retailer's shopping experience. The authors aim to highlight the growing role of returns in e-commerce and to point out the logistical challenges of operating retail shops in an omnichannel model. The authors presented the evolution and development of sales channels, as well as focusing on the essence of the logistical handling of sales in the omnichannel model. The article also presents the formal and legal aspects related to the customer's return of purchased goods. The theoretical part, based on the literature on the subject, was enriched with the results of own research conducted both among customers of online shops and an analysis of the return handling processes at Decathlon Sp. z o.o.